2021
DOI: 10.3346/jkms.2021.36.e121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emergency Care-related Health Policies during the COVID-19 Pandemic in Korea: a Quasi-Experimental Study

Abstract: Background The purpose of this study was to review the nationwide emergency care-related health policies during the coronavirus disease 2019 (COVID-19) pandemic disaster in Korea and to analyze the effects of the policies on the safety of patients who visit emergency departments (EDs) during this period. Methods This study is a quasi-experiment study. The study population was patients who visited all 402 EDs in Korea between December 31, 2019 and May 13, 2020, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 26 publications
5
31
0
Order By: Relevance
“…The decrease in the total number of ED visits in the current study is consistent with the previous ones [ 21 24 ]. It may be due to general hesitancy or ED transport refusal among patients [ 43 , 44 ] and limited resources under new policies [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decrease in the total number of ED visits in the current study is consistent with the previous ones [ 21 24 ]. It may be due to general hesitancy or ED transport refusal among patients [ 43 , 44 ] and limited resources under new policies [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the coronavirus disease of 2019 (COVID-19) pandemic has also imposed strict quarantine policies such as large-scale screening for viral symptoms and visitor restrictions [ 18 ], thus making the ED more unsuitable for death [ 19 , 20 ]. Although the total number of ED visitations decreased during the pandemic in the United States [ 21 , 22 ] and Korea [ 23 , 24 ], the ED mortality rate significantly increased after COVID-19 in Korea [ 25 ]. Hence, there is growing interest in providing and even initiating palliative care for terminal patients in ED [ 26 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pak et al also reported that the application of appropriate emergency care policies during the COVID-19 pandemic in Korea improved the safety of all emergency patients and reduced hospital mortality [ 22 ]. On the other hand, the temporary ED closures because of unpredicted COVID-19 exposure resulted in an increase in in-hospital mortality rates of emergency patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate data is filtered by a data processing system. The NEDIS data is updated in real time by the National Emergency Medical Center and approved annually by National Statistics for data quality management [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%